LITERASI DAN INTERAKSI DUNIA MAYA PADA SUATU INDIVIDU BESERTA CONTOHNYA DALAM BENCANA ALAM - Zahwa Kania Putri; Nurul Janah, Salsabilla Citra, Sulistiasih (ADISAM PUBLISHER, 2024)
Social interaction and cyber literacy are the main topics in the digital era today. Social media has become the main platform for people to interact and share information. However, low digital literacy and a lack of understanding of social realities in cyberspace can have negative impacts, such as social deviance and social media addiction. This research uses a literature study method to determine the factors that can influence interaction and literacy in cyberspace and their impacts. The results show the importance of digital skills, ethics, and vigilance when interacting on social media to create functional and positive interactions. Therefore, digital literacy is a necessary skill for individuals to interact healthily and responsibly in cyberspace.